2021
DOI: 10.1177/0308518x20987229
|View full text |Cite
|
Sign up to set email alerts
|

Geography and the theory of uneven and combined development: Theorizing uniqueness and the return of China

Abstract: As societal interaction and combination play a vital role in shaping spatio-temporal development paths, meta-theories of uneven development should give way to a relational meta-theory of uneven and combined development (U&CD). U&CD examines at multiple levels of abstraction not just internal causal mechanisms governing the trajectories of individual societies but also causal mechanisms deriving from societal interaction in a world of multiple unevenly developed societies and multiple development pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 56 publications
2
7
0
Order By: Relevance
“…The first indicator reflects individual variability relative to the world average, so that the measure of inequality is independent of the unit of income denomination. It thus complies with Krtschas (1994) criterion. The second indicator shows the income redistribution from areas with a negative sign to those with a positive sign.…”
Section: Global Inequality In the Age Of Globalizationsupporting
confidence: 62%
See 1 more Smart Citation
“…The first indicator reflects individual variability relative to the world average, so that the measure of inequality is independent of the unit of income denomination. It thus complies with Krtschas (1994) criterion. The second indicator shows the income redistribution from areas with a negative sign to those with a positive sign.…”
Section: Global Inequality In the Age Of Globalizationsupporting
confidence: 62%
“…With rare exceptions, peripheral industrialization was patchy, limited to few territorial areas, and dependent on the global market and the variable relocation choices of multinational firms (Arrighi and Drangel 1986;Arrighi et al, 2003;Selwyn 2015). The most notable exception is China which adopted its peculiar model of integration into the global economy, comprising a predominant role of the State in terms of public ownership, planning of strategic industries and strict banking and financial regulation, alongside a broad openness to foreign direct investment by multinational capital (Herrera 2014;Dunford et al 2021;Macheda and Nadalini 2022). Because of these changes in the international division of labour, in recent decades the weight of exports of goods and services on world Gross Domestic Product (GDP) has more than doubled, rising from 12.8% in 1970 to 28.3% in 2019, with a peak of 31% in 2008 (World Bank data).…”
Section: Introductionmentioning
confidence: 99%
“…The BRI has come to symbolise the more visible role of the state in carving out policy space for industrial development, but as this article has shown, its expansion has been underpinned by a hybridisation of productive and financialised accumulation logics. Together with the resulting state transformations that have empowered the Serbian state, the insights generated here reinforce the value of an analytical lens that privileges continuity, as well as disjuncture, in understanding capitalist development as an uneven and combined process Dunford et al, 2021;Furlong, 2020;Rolf, 2021).…”
Section: Discussionsupporting
confidence: 53%
“…Transnational state projects such as state-backed global infrastructure projects, policies supporting the outflow of Chinese FDI and the externalisation of Chinese SOEs are contextualised within the country's integration into world markets and post-Mao economic transition that has spurred development but also a massive concentration of surplus capital and a growing gap between domestic overinvestment and under-consumption in the wake of the global financial crisis (Hung, 2008;Rolf, 2019). In the wake of the crisis, the state provided a major stimulus package that became the main engine of global growth but that has led to excess capacity from debt-fuelled overinvestment, especially at the sub-national level in infrastructure and housing (Dunford et al, 2021;Wu, 2021). The growing structural imbalance in the Chinese economy is the backdrop to the transnationalisation of state capital needed to address issues of domestic overcapacity by securing new markets for the absorption of surplus capital.…”
Section: Marxist and Neo-gramscian Approaches: China In Global Capita...mentioning
confidence: 99%
See 1 more Smart Citation